Analisis Vegetasi Mangrove di Pulau Arar Distrik Mayamuk Kabupaten Sorong - Muh Ishar Difinubun; Lina Kumalasari; Nurul Meishah; Sohibul Ma'arif (Jurnal Aquafish Saintek, 2022)
Sorong Regency which has the potential of mangrove forest resources, namely the Aimas District, Mayamuk District, Segun District, Beraur District to Klabot District with a mangrove forest area of ​​33,142 Ha. This research was carried out in July - July 2022, aims to determine the mangrove vegetation on Arar Island, Mayamuk District, push. Observations were made with a combination of the path method and the checkered line method as well as parameter measurements environment as supporting data. Vegetation analysis includes species density, relative density, species frequency, relative frequency, species dominance, relative dominance, and important value index. Found 3 types of mangroves, namely Avicennia lanata, Rhizophora apiculata, and Rhizophora mucronata. The type of mangrove Rhizophora mucronata is found in all stations observations and has the highest INP value in all categories, both in the category of trees (178.04%), saplings (200%), and seedlings (154.64%). The high INP reflects the condition of the mangrove vegetation at the study site in a good and hasn't changed much. The environmental parameters at each station show the appropriate value for mangrove growth.